Automated sex identification from 3D skulls based on patch representations for forensic examinations - Arigbabu, Olasimbo Ayodeji (2019)
This thesis introduces new perspective of addressing skull sex determination by investigating the possibility of using computer vision based solutions for sex determination from skull data, and developing new algorithms tailored for mitigating the underlying problems experienced in the conventional forensic sex determination methods.